The Yin and Yang of Antiviral Innate Immunity in Central Nervous System - Zohaib, Ali; Sarfraz, Adeel; Muhammad Kaleem, Qari; Ye, Jing; Niaz Mughal, Mudassar; Tariq Navid, Muhammad; Ahmed Khan, Faheem; Duan, Xiaodong; Zhu, Bibo; Wan, Shengfeng; Cao, Shengbo (Current Pharmaceutical Design, 2016)
The innate immune system provides protection against invading neurotropic viruses. It acts as the first line of defense against invading viruses and plays an elementary role in their pathogenesis. The list of viruses capable of infecting human central nervous system (CNS) is quite long, most important of them are Japanese Encephalitis virus (JEV), rabies virus, West Nile virus (WNV), herpes simplex virus (HSV), St. Louis encephalitis virus (SLEV), La Crosse virus, tick borne encephalitis virus (TEBE) and polio virus. Germ line pattern recognition receptors (PRRs) such as Toll like receptors (TLRs), nucleotide binding oligomerization domain (NOD) - like receptors (NLRs), retinoic acid-inducible gene I (RIG-I) -like helicases or RIG-I-like receptors (RLRs) and cytosolic DNA sensors recognize the pathogen associated molecular patterns (PAMPs) and initiate an immune response against invading pathogen. Although PRRs were originally characterized in peripheral immune cells but accumulating evidence also suggest their crucial roles in CNS to combat against neurotropic viruses. In this review, we will highlight the recent developments in our understating of the mechanisms by which PRRs in resident brain cells provide protection against invading neurotropic viruses.
Keywords: Central nervous system